Apps for Those Who Help Themselves: Mobile Self-Guided Interventions for Adolescent Mental Health - Seko, Yukari; Kidd, Sean; Wiljer, David (AoIR Selected Papers of Internet Research, 2013)
The exponential growth in the use of mobile phone has brought new opportunities for supporting adolescent mental healthcare. Clinical experts increasingly leverage mobile phone technology for patient self-assessments, self-paced mood charting, and virtual coaching. Yet, little has been studied regarding the depth and the breadth of evidence in the area of mobile self-guided interventions and their implications to adolescent mental health. This paper offers a scoping review of current mobile phone use in self-guided interventions for adolescents examines the key design principles in the development of these tools. The findings indicate a range of new challenges and affordances. While mobile tools are welcomed by healthcare professionals as an engaging platform for involving patients in their own care, it is crucial to critically consider ethical issues arising with mobile interventions, such as confidentiality, privacy, and potential loss of control caused by a forced self-surveillance and regulation.